PENGARUH KEPEMIMPINAN TERHADAP DISIPLIN KERJA PEGAWAI KANTOR CAMAT TAMBANG KABUPATEN KAMPAR - Hendrayani, Hendrayani; Angraini, Hersa Vivi (Eko dan Bisnis: Riau Economic and Business Review, 2022)
The purpose of this study was to determine and analyze the influence of leadership on work discipline for employees at the Mining District Office of Kampar Regency. The population of this study were all 33 employees of the Sub-district Mining Office of Kampar Regency and the research sample used the census method (33 people). The research method used is descriptive and quantitative methods and then analyzed using a simple linear regression method. The results of the recapitulation of the average value of the Supervision variable are 3.82, meaning that the respondents' answers to all statements of the Employee leadership variable are Agree (good). Based on the results of the t-test, it was found that the value of t_count > t_table (6.545 >2.039) and a significance <0.05 (0.000 <0.05). This means that leadership has a positive and significant effect on employee work discipline. The R square value of 0, 580 or 58.0% means that leadership has an influence on work discipline for employees at the Mining District Office of Kampar Regency by 58.0% and the rest (100-58, 0) 42.0% influenced by other variables not examined in this study.